2016
DOI: 10.2337/dc16-0232
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction of Developing Type 2 Diabetes by Plasma Acylcarnitines: A Population-Based Study

Abstract: OBJECTIVEAcylcarnitines were suggested as early biomarkers even prior to insulin resistance in animal studies, but their roles in predicting type 2 diabetes were unknown. Therefore, we aimed to determine whether acylcarnitines could independently predict type 2 diabetes by using a targeted metabolic profiling approach. RESEARCH DESIGN AND METHODSA population-based prospective study was conducted among 2,103 communityliving Chinese individuals aged 50-70 years from Beijing and Shanghai with a mean follow-up dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
114
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(130 citation statements)
references
References 44 publications
10
114
2
Order By: Relevance
“…Few studies have reported changes in these metabolites. One study noted elevated levels of malonylcarnitine in incident T2D (Sun et al, 2016) and Mai et al (2013) reported that the sum of malonylcarnitine and 3-OHbutyrylcarnitine increased in T2D subjects compared to subjects with normal glucose tolerance, impaired fasting glucose, and impaired glucose tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have reported changes in these metabolites. One study noted elevated levels of malonylcarnitine in incident T2D (Sun et al, 2016) and Mai et al (2013) reported that the sum of malonylcarnitine and 3-OHbutyrylcarnitine increased in T2D subjects compared to subjects with normal glucose tolerance, impaired fasting glucose, and impaired glucose tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…The intra‐assay coefficients of variation for blood glucose were <2.5%. Diabetes was defined by the presence of any of the following: (i) self‐reported doctor‐diagnosed diabetes; (ii) current use of insulin or oral hypoglycemic agents; and (iii) fasting blood glucose ≥7.0 mmol/L.…”
Section: Methodsmentioning
confidence: 99%
“…By using a targeted metabolomic approach, we detected a total of 34 plasma acylcarnitines among 2103 subjects that completed the 6-year follow-up in the NHAPC study. 49 It was shown, for the first time, that a panel of acylcarnitines, especially with long chains, could substantially improve predictive ability for incident T2D, because the AUC improved to 0.89 in the full model (vs 0.73 in the conventional model including lifestyle factors, family history of diabetes, body mass index, fasting glucose, and HbA1c). Nonetheless, the roles of different acylcarnitines in cardiometabolic health need to be elucidated in further studies.…”
Section: Application Of Metabolomics For Disease Predictionmentioning
confidence: 98%